2002
DOI: 10.1590/s1516-14392002000300010
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Computer Application to Simulate Porous Structures

Abstract: Geometric modeling is an important tool to evaluate structural parameters as well as to follow the application of stereological relationships. The obtention, visualization and analysis of volumetric images of the structure of materials, using computational geometric modeling, facilitates the determination of structural parameters of difficult experimental access, such as topological and morphological parameters. In this work, we developed a geometrical model implemented by computer software that simulates rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Considering that pores are cylindrical, Reis et al [26] developed an equation that uses specific pore volume, theoretical density, and specific surface experimental measurements to directly evaluate structural connectivity. The model presented here can generate connectivity curves from experimental parameters such as specific surface area, specific pore volume, and skeletal density, as shown in Eq.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that pores are cylindrical, Reis et al [26] developed an equation that uses specific pore volume, theoretical density, and specific surface experimental measurements to directly evaluate structural connectivity. The model presented here can generate connectivity curves from experimental parameters such as specific surface area, specific pore volume, and skeletal density, as shown in Eq.…”
Section: Characterizationmentioning
confidence: 99%
“…The o-Ps intensity of s 3 is high and increases with aging temperature. In contrast, the intensity of s 4 is lower and decreases with temperature increases.The results obtained with the model developed by Reis et al[26] are shown in…”
mentioning
confidence: 99%
“…To create randomized shapes, the vertices of existing unit cells can be varied in a random fashion, as is the case for Zhang et al [61]'s work. A similar method is captured in the work of Reis et al [62]. They create a network of struts that it subtracted from an original design space.…”
Section: Rve Variation Based On Random and External Sourcesmentioning
confidence: 99%